Teaching behavioural sciences: looking back at the Colombo experience - Olupeliyawa, A.M.; Gooneratne, I.K.; Wickramasinghe, W.A.K.K.; Thilakaratne, M.S.B.; Karunathilake, I.M.; Samarasekera, D.D. (South-east Asian Journal of Medical Education, 2008)
Purpose: To review studies conducted to evaluate the output of the Behavioural Sciences Stream (BSS) of the Faculty of Medicine, Colombo in terms of achieving its objectives and with regards to its teaching/ learning and assessment methods. Data sources, Study selection and Data extraction: A manual search was conducted using official faculty publications, reports of student research and conference proceedings. Pubmed/Medline indexed articles were also reviewed using the keywords; communication skills, ethics & professionalism, teaching / learning methods, evaluation methods, behavioural sciences. From a total of 384 hits 19 articles were reviewed. Results: Studies conducted to evaluate the outcome of BSS conclude that the majority of students felt that they achieved the objectives of developing the necessary skills and professionalism. However the patients thought that some aspects were not adequately practiced. Suggestions for improving teaching/ learning methods to achieve these skills included interactive activities, simulated and standardized patient interviews, and reinforcement of BSS inputs during professorial clinical rotations. Similar methods are practiced successfully worldwide. Many studies showed that students prefer to be assessed in the ward setting. Such methods of assessment in other medical curricula include assessment of video taped student patient interactions, stations assessing behavioural skills at Objective Structured Clinical Examinations (OSCE) and assessments as part of clinical evaluations. Conclusions: Introducing behavioural sciences teaching has been successful as a pioneering effort in Sri Lanka. BSS teaching and assessments should be more integrated with ward teaching and clinical assessments for optimal achievement of its objectives.
Keywords: Behavioural Sciences Stream; teaching